Geographical scale and the role of firm migration in spatial economic dynamics - Leo JG Van Wissen; Veronique Schutjens (European Regional Science Association (ERSA), 2005)
Spatial economic change can be decomposed in it's demographic constituents firm formation, closure, relocation and growth. This paper focusses on the role of relocation in the balancing equation of spatial economic dynamics: Total Change(zone i) = New firms(i)-Closures(i)+ Growth(i)-Decline(i)+ Inmoves(i)-Outmoves(i). Whereas the other components are scale invariant (i.e. a firm birth is a birth whether measured at the local or the regional level) for firm relocation the geographical scale is very important. The larger the size of the region, the smaller the number of border crossing relocations. The question about the role of firm migration in regional economic change can therefore only be answered taking into account the geographical scale. In this paper we will answer this question for various geographical scales. The data that we use are from the longitudinal business register of the province of Gelderland, in the east of the Netherlands, covering the period 1988-2002.
Keywords: 330